Measuring the Technical Efficiency in the Traditional Private Commercial Banks in Syria using the FDEA, DEA Method - A Comparative Study on Private Banks Listed in Damascus Securities Exchange - (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This paper aims to assess the technical efficiency of the commercial private banks in Syria, in accordance with FDEA and DEA, and to detect a difference in the efficiency according to FDEA and DEA, based on data (2010,2021). The research sample included 11 commercial private banks listed on the Damascus Securities Exchange. Adopted an intermediation approach, Inputs are capital, employment and deposits, and outputs are loans to other banks and customers. We use a model (CCR) and input-oriented method. The concept of triangular numbers and the alpha-level approach are used in the (FDEA). The results indicated that Syria's commercial private banks did not have the technical efficiency according to FDEA, DEA, Fuzzy supper (SBM). On the other hand, the Bank of Syria and Gulf enjoyed better technical efficiency among the banks studied, while the Bank of Syria and overseas was the worst efficient. There was also a difference in the FDEA results and the DEA results, but FDEA was the best to determine efficiency from the DEA, and did not give exaggerated results, as confirmed by the Fuzzy supper (SBM). More over, presence of efficient banks under DEA, but not under FDEA, indicates that FDEA has a greater potential to distinguish between efficient and inefficient banks than traditional data envelopment analysis (DEA), and that the efficiency of Syria's traditional banks is affected by fuzziness and randomness.